Enterprising behaviour of ordinary people - Van Gelderen, Marco (Psychology Press, 2000)
Starting out with the idea that everybody is in principle capable of enterprising behaviour, the concept of enterprise is applied to non-business people as well as business people. A random sample of people is asked to furnish an example of enterprising behaviour that they have shown themselves. Further, they are asked what is enterprising about this behaviour. The results show that in different realms of enterprising behaviour different dimensions of enterprise are mentioned. For example, people giving an example from their leisure time regard merely being active as enterprising, employees mention risky elements in their work, business owners emphasize autonomy, and students regard it as enterprising that they work for their professional or personal development. So people can be enterprising in different areas of life and in different manners. Obtaining a domain of enterprising behaviours and dimensions is a first step in constructing a scale of ''enterprising behaviour of ordinary people''.
Keywords: Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management